Latin American Economic History: An Introduction to Daily Life, Debt, and Development - Molly C. Ball (Routledge, 2025)
Latin American Economic History: An Introduction to Daily Life, Debt, and Development guides readers through significant features and developments in the region's economic history from independence through 2022. In approachable language, the book introduces readers to relevant New Economic History concepts and explains important characteristics of Latin America, such as the region's high volatility, rapid urbanization experience, the continued prominence of commodities, and its culture of informality. The volume provides explicit connections between culture, politics, and economics over five distinct time periods. Readers will learn how Cinco de Mayo featured into foreign debt repayments in the nineteenth century, how novels like Gabriel García Márquez'sOne Hundred Years of Solitude reflected on the expansion of railroads during a period of export-led growth, and how a United States federal reserve interest hike in 1979 sent the region into the Lost Decade. When considered collectively, the region's economic trajectory demonstrates that development does not always accompany economic growth. This is an accessible introductory text with clear definitions and discussions of relevant economic concepts, which will be a valuable resource for students of Latin American economic, cultural, and political history.
Keywords: 330; United Fruit Company; Human Development Index; Gini coefficient; Monroe Doctrine; Cinco de Mayo; Baring Crisis; Human capital; Rio Branco Law; 1919 Peru General Strike; Mexican Revolution; 1978 ABC Metalworker's Strike; Cuban Revolution; Economic Commission on Latin America; General Agreement on Tariffs and Trade; 1982 Peso Crisis; NAFTA; Nicolás Maduro; Industrialization